Reference equation for maximal voluntary ventilation in children and adolescents. Issue 2 (19th November 2019) - Silva, Jaksoel C.; Carvalho, Ideza E.; Dal Corso, Simone; Lanza, Fernanda C.
Abstract: Objectives: To develop reference equations of maximal voluntary ventilation (MVV) in children and adolescents, and to test the validity and reproducibility of MVV. Study Design: Cross‐sectional study. Patient‐Subject selection: A total of 348 healthy volunteers (6‐17 years)—248 for the development of reference equations and 100 to test the validity— were selected. Methodology: Spirometry and MVV were performed. Volunteers were instructed to breathe quickly and strongly to estimate the MVV. Independent variables tested were age, sex, weight, height, and pulmonary function. Results: All volunteers (50% boys) had a normal pulmonary function. Mean MVV was 66.3 (17.8) L/minute for children and 118.8 (20.0) L/minute for adolescents. The equation developed for children was MVV = 4.865 + (forced expiratory volume in the first second [FEV1] × 16.257) + (peak expiratory flow [PEF] × 7.621); for adolescents was MVV = −25.450 + (FEV1 × 11.591) + (PEF × 6.672) + (sex × 12.179) + (age × 3.613). No significant differences were observed between measured and predicted MVV in children (64.6 [10.3] vs 64.6 [8.5] L/minute; P = .34) or adolescents (111.8 [23.4] vs 113.1 [22.8] L/minute, P = .12). The intraclass correlation coefficient between measured and predicted MVV was 0.95 (0.91‐0.97) for children and 0.90 (0.82‐0.94) for adolescents. The mean bias of Bland‐Altman analysis was −0.8 L/minute for children and −2.7 L/minute for adolescents. Conclusions: Normative values for MVV were established for children and adolescents, additionally, these equations are reproducible and it can be used to determine the respiratory impairments in the pediatric population.